Resin, resin composition and cured film

By using polyamic acid ester resin formed by polymerization of alicyclic tetracarboxylic dianhydride and aromatic diamine, the problems of dielectric properties and thermal stress in the packaging process of traditional polyimide materials are solved, and the combination of low dielectric constant, low dielectric loss and low curing temperature is achieved, and the reliability and resolution of the packaging are improved.

CN119912689APending Publication Date: 2025-05-02HUAWEI TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311433893.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-30
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Traditional polyimide materials are difficult to have low dielectric constant, low dielectric loss and low curing temperature during packaging, which leads to difficulty in reducing thermal stress and insufficient packaging reliability.

Method used

Polymerized by alicyclic tetracarboxylic dianhydride and aromatic diamine, forming a polyamic acid ester resin, and introducing fluorine-containing atoms and alicyclic structures to reduce dielectric constant and dielectric loss, while improving the transparency and heat resistance of the cured film.

Benefits of technology

The resin is achieved with low dielectric constant, low dielectric loss and low curing temperature, effectively reducing thermal stress during packaging and improving the reliability and resolution of packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912689A_ABST
    Figure CN119912689A_ABST
Patent Text Reader

Abstract

The invention discloses resin, a resin composition and a cured film. The resin is a compound as shown in a formula I; wherein R1 and R2 are respectively and independently hydrogen atoms, alkyl groups, aryl groups, aryl groups or monovalent organic groups, and R1 and R2 are not hydrogen atoms at the same time; x is selected from tetravalent alicyclic organic groups; y1 is selected from divalent aromatic organic groups; y2 is selected from a fluorine-containing divalent aromatic organic group; n is selected from a natural number from 30 to 150, and m is selected from a natural number from 30 to 150. And # imgabs0 #.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polymer films, and in particular, to resins, resin compositions and cured films. Background Art

[0002] With the continuous upgrading of electronic products, emerging markets such as smartphones, 5G, and AI have put forward higher requirements on packaging technology, making packaging technology develop in the direction of high integration, three-dimensional, and ultra-fine pitch interconnection.

[0003] Re-distribution layer (RDL) packaging technology is often used in the packaging of electronic components. Multi-layer wiring technology allows the interlayer insulation layer and metal wires to be repeatedly and alternately distributed, and has higher requirements for the tightness between the insulation layer and the metal wire, resistance to high and low temperature impact, and resistance to high temperature storage. The coefficient of thermal expansion (CTE) of the traditional polyimide material cured film is usually 40-70ppm / K, which is higher than copper (15-20ppm / K), and the curing temperature generally needs to be above 350℃. Cracks and delamination often occur between the insulation layer and the metal wire during the high-temperature imidization process. In addition, the electronic components in the packaging structure are also prone to warping and deformation due to excessively high curing temperatures.

[0004] As the packaging structure tends to be miniaturized, the distance between the electronic components inside it decreases, which will cause signal transmission delays and make it difficult to meet the signal processing needs of high-frequency and high-speed development. Therefore, the requirements for the dielectric constant and dielectric loss of polyimide materials are getting higher and higher. At present, it is difficult for traditional polyimide materials to have the properties of low dielectric constant, low dielectric loss and low curing temperature at the same time, making it difficult to effectively reduce the thermal stress generated during the packaging process and improve the reliability of the packaging. Summary of the invention

[0005] The present application provides a resin, a resin composition and a cured film. The resin can have low dielectric constant, low dielectric loss and low curing temperature, effectively reduce the thermal stress generated during the packaging process, and improve the reliability of the packaging.

[0006] The present application provides a resin, which is a compound represented by formula I;

[0007]

[0008] wherein R1 and R2 are each independently a hydrogen atom, a hydrocarbon group, an aryl group, an aromatic hydrocarbon group or a monovalent organic group, and R1 and R2 are not hydrogen atoms at the same time;

[0009] X is selected from a C4-C10 tetravalent alicyclic organic group;

[0010] Y1 is selected from divalent aromatic organic groups;

[0011] Y2 is selected from fluorine-containing divalent aromatic organic groups;

[0012] n is a natural number selected from 30 to 150, and m is a natural number selected from 30 to 150.

[0013] In the above scheme, alicyclic tetracarboxylic dianhydride is used as the dianhydride component, and aromatic diamine (at least part of the aromatic diamine monomers in the diamine monomers are fluorine-containing aromatic diamines) is used as the diamine component to polymerize to form a polyamic acid ester resin, and an alicyclic X group is introduced into the resin, and a fluorine atom is introduced into the Y2 group, which can improve the transparency of the resin and improve the tensile properties, heat resistance, patterning resolution and adhesion of the resin while reducing the dielectric constant of the resin. Due to the introduction of fluorine atoms and alicyclic rings, the transparency of the polyimide cured film is improved, so that the cured film has excellent i-line transmittance and improved resolution.

[0014] In some embodiments, X is selected from at least one of the following structures:

[0015]

[0016] In some embodiments, the Y1 is selected from the group of the structure shown in Formula II;

[0017]

[0018] In Formula II, Z is selected from any one of -CH2-, -O-, -C=O- and -S=O-.

[0019] In some embodiments, Y2 is selected from at least one of the following structures:

[0020]

[0021] In some embodiments, at least one of R1 and R2 is selected from a monovalent organic group without a saturated bond.

[0022] In a second aspect, the present application provides a method for preparing the resin according to the first aspect, the method comprising:

[0023] Under the protection of inert gas, alicyclic dianhydride is reacted with an esterification agent to generate alicyclic diester diacid, and then alicyclic diester diacid is reacted with an acyl chloride agent to generate a diester diacid chloride solution;

[0024] Aromatic diamine monomer solution is added to the diester dichloride solution to carry out polycondensation reaction, followed by precipitation treatment to obtain polyamic acid ester resin, wherein the aromatic diamine monomer includes fluorine-containing aromatic diamine monomer and non-fluorine-containing aromatic diamine monomer.

[0025] In some embodiments, the alicyclic dianhydride is selected from at least one of cyclobutanetetracarboxylic acid, cyclobutanetetracarboxylic dianhydride, cyclohexanetetracarboxylic acid, cyclohexanetetracarboxylic dianhydride, cyclopentanetetracarboxylic acid, cyclopentanetetracarboxylic dianhydride, 2,4-dimethyl-1,2,3,4-cyclobutanetetracarboxylic acid, 2,4-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, and bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride.

[0026] In some embodiments, the esterification agent is selected from at least one of 2-hydroxyethyl methacrylate, ethanol, propanol, n-butanol, hydroxypropyl methacrylate, and 2-hydroxy-1,3-propylene glycol 2-acrylate.

[0027] In some embodiments, the ratio of the molar amount of the alicyclic dianhydride to the molar amount of the esterification agent is 1:(2-2.1).

[0028] In some embodiments, the acyl chloride reagent is selected from thionyl chloride, phosphorus trichloride, phosphorus chloride, oxalyl chloride or phosgene.

[0029] In some embodiments, the ratio of the molar amount of the alicyclic dianhydride to the molar amount of the acyl chloride reagent is 1:(1-1.05).

[0030] In some embodiments, the aromatic diamine monomer is selected from 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 1,4-bis(4-aminophenoxy)benzene, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, 1,5-naphthalenediamine, 2,6-naphthalenediamine, bis(4-aminophenoxyphenyl)sulfone, bis(3-aminophenoxyphenyl)sulfone, bis(4-aminophenoxy)biphenyl, bis{4-(4-aminophenoxy)phenyl}ether, 4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 2,2'-diethyl-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, At least one of 3,3'-diethyl-4,4'-diaminobiphenyl, 2,2',3,3'-tetramethyl-4,4'-diaminobiphenyl, 3,3',4,4'-tetramethyl-4,4'-diaminobiphenyl, 2,2'-bis(trifluoromethyl)benzidine, 2,6,2',6'-tetrakis(trifluoromethyl)benzidine, 2,2-bis[4-(3-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis(4-anilino)hexafluoropropane, 2,2-bis(3-anilino)hexafluoropropane and 2,2-bis(3-amino-4-toluoyl)hexafluoropropane.

[0031] In some embodiments, the molar weight of the alicyclic dianhydride is nA, the molar weight of the aromatic diamine monomer is nB, and 1≤nA:nB≤1.1.

[0032] In some embodiments, the precipitation step comprises:

[0033] The polyamic acid ester resin solution after the cross-linking reaction is added to a precipitant for precipitation treatment, and the precipitated product is dried; wherein the precipitant includes at least one of water, methanol, ethanol, propanol, butanol, hexane, butyl cellosolve or toluene.

[0034] In some embodiments, the mass ratio of the amount of the precipitant to the polyamic acid ester resin solution after the cross-linking reaction is (1-50):1.

[0035] In some embodiments, the drying temperature is 10°C to 150°C.

[0036] In a third aspect, the present application provides a resin composition, comprising the resin according to the first aspect of claim.

[0037] In some embodiments, the weight average molecular weight of the resin is 5,000 to 100,000.

[0038] In some embodiments, based on 100% by mass of the resin, the resin composition further comprises 0.01% to 10% by mass of a polymerization inhibitor.

[0039] In some embodiments, based on the weight of the resin as 100%, the resin composition further includes a solvent accounting for 100% to 1000% by weight, and the solvent includes at least one of an alcohol organic solvent, a ketone organic solvent, an ether organic solvent, an ester organic solvent and an amide organic solvent.

[0040] In some embodiments, based on the weight of the resin as 100%, the resin composition includes 0.1% to 20% by weight of a photopolymerization initiator, and the photopolymerization initiator is selected from at least one of benzoin and its derivatives, acetophenone derivatives, α-hydroxyketone derivatives, acylphosphorus oxides, oxime compounds, aromatic ketone compounds and metallocene compounds.

[0041] In some embodiments, based on 100% by mass of the resin, the resin composition further comprises 1% to 50% by mass of a photopolymerizable compound.

[0042] In some embodiments, the resin composition further includes a photopolymerizable compound, which includes at least one of 2-hydroxymethyl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, 2-hydroxymethyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxybutyl acrylate, glycidyl acrylate, glycidyl acrylate, glycidyl methacrylate, glycidyl methacrylate, ethylene glycol diethyl ether methacrylate, ethylene glycol diethyl ether acrylate, and polyethylene glycol methacrylate.

[0043] In some embodiments, based on 100% by weight of the resin, the resin composition includes 0.05% to 2% by weight of an inhibitor, 1% to 5% by weight of a photopolymerization initiator, 5% to 20% by weight of a photopolymerizable compound, and 200% to 300% by weight of a solvent.

[0044] In a fourth aspect, the present application provides a cured film, wherein the cured film is prepared from the resin composition according to the third aspect.

[0045] In some embodiments, when the thickness of the cured film is 10±1 μm, the thermal expansion coefficient at 100° C. to 200° C. is ≤20 ppm / K.

[0046] In some embodiments, when the thickness of the cured film is 10±1 μm, the elongation at break of the cured film is ≥50%.

[0047] In some embodiments, when the thickness of the cured film is 10±1 μm, the dielectric constant at a frequency of 40 GHz is ≤2.7.

[0048] In some embodiments, when the thickness of the cured film is 10±1 μm, the light transmittance at a wavelength of 450 nm in the visible light region is ≥85%.

[0049] In a fifth aspect, the present application provides an electronic device, wherein the electronic device comprises the above-mentioned cured film, or the electronic device comprises a cured film formed by curing the above-mentioned resin composition.

[0050] In some embodiments, the cured film serves as a protective layer, a passivation layer, an interlayer insulating layer, a buffer layer, a planarization layer, a shielding layer, or a rewiring layer in the electronic device. DETAILED DESCRIPTION

[0051] The embodiments described below are exemplary and are only used to explain the present invention, but should not be construed as limiting the present invention.

[0052] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.

[0053] In addition, in order to better illustrate the present application, numerous specific details are given in the following specific embodiments. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In some examples, methods, means, components and circuits well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present application.

[0054] <First aspect>

[0055] The present application provides a resin, which is a compound represented by formula I;

[0056]

[0057] wherein R1 and R2 are each independently a hydrogen atom, a hydrocarbon group, an aromatic group or a monovalent organic group, and R1 and R2 are not hydrogen atoms at the same time;

[0058] X is selected from tetravalent alicyclic organic groups;

[0059] Y1 is selected from divalent aromatic organic groups;

[0060] Y2 is selected from fluorine-containing divalent aromatic organic groups;

[0061] n is a natural number selected from 30 to 150, and m is a natural number selected from 30 to 150.

[0062] In the above scheme, alicyclic tetracarboxylic dianhydride is used as the dianhydride component and aromatic diamine (at least part of the aromatic diamine monomers in the diamine monomers are fluorinated aromatic diamines) is used as the diamine component to polymerize to form a polyamic acid ester resin, which can reduce the dielectric constant of the resin while improving the tensile properties, heat resistance, patterning resolution and adhesion of the resin. Due to the introduction of fluorine atoms and alicyclic rings, the transparency of the polyimide cured film is improved, so that the cured film has excellent i-line transmittance and improved resolution.

[0063] In some embodiments, X is selected from a tetravalent alicyclic organic group, which can be a C4-C10 tetravalent alicyclic organic group, which is introduced by alicyclic tetracarboxylic acid dianhydride, and the carbon atoms in the tetravalent alicyclic organic group can also be combined by chemical bonds to form a bridged ring. The alicyclic organic group in the structure can improve the transparency of the resin, improve the heat resistance of the resin, and reduce the thermal expansion coefficient.

[0064] In some embodiments, at least one of R1 and R2 is selected from a monovalent organic group without a saturated bond.

[0065] In some embodiments, when R1 and R2 are independently selected from hydrocarbon groups, they can be alkyl groups or alkenyl groups. Preferably, R1 and R2 are independently selected from alkyl groups. The alkyl group can be a C1-C10 alkyl group, which is a chain alkyl group. The chain alkyl group can be a straight chain alkyl group or a branched chain alkyl group. The lower limit of the number of carbon atoms in the C1-C10 alkyl group is 1, 2, 3, 4, 5, and the upper limit is 3, 4, 5, 6, 8, 10. Preferably, a C1-C6 chain alkyl group is selected. Specifically, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, isopentyl, neopentyl, hexyl, octyl, nonyl, and decyl can be cited.

[0066] In some embodiments, when R1 and R2 are independently selected from aryl groups, the aryl group may be phenyl, phenylalkyl, biphenyl, condensed ring aromatic hydrocarbon group (such as naphthyl, anthracenyl, phenanthryl). Examples of aryl groups include phenyl, benzyl, biphenyl, p-tolyl, o-tolyl, m-tolyl, naphthyl, anthracenyl, and phenanthryl.

[0067] In some embodiments, X is selected from at least one of the following structures:

[0068]

[0069] In some embodiments, Y1 is selected from a divalent aromatic organic group, and the aromatic organic group can provide suitable rigidity to the resin. Specifically, Y1 is selected from a group having a structure shown in Formula II;

[0070]

[0071] In Formula II, Z is selected from any one of -CH2-, -O-, -C=O- and -S=O-.

[0072] In some embodiments, Y2 is selected from a fluorine-containing divalent aromatic organic group. The fluorine-containing divalent aromatic organic group can provide the resin with an excellent low dielectric constant and improve the tensile properties of the resin.

[0073] In some embodiments, Y2 is selected from at least one of the following structures:

[0074]

[0075] <Second Aspect>

[0076] The present application provides a method for preparing the resin described in the first aspect. In the present application, there is no particular limitation on the method for preparing the photosensitive resin. In some embodiments, the method includes:

[0077] S1, under the protection of inert gas, reacting alicyclic dianhydride with an esterification reagent to generate alicyclic diester diacid, and then reacting alicyclic diester diacid with an acyl chloride reagent to generate a diester diacid chloride solution;

[0078] S2, adding an aromatic diamine monomer solution to the diester dichloride solution to carry out polycondensation reaction, and then performing precipitation treatment to obtain a polyamic acid ester resin.

[0079] The preparation method of the resin provided in the present application maintains excellent storage stability, excellent comprehensive performance and good adhesion through regulation.

[0080] In some embodiments, the alicyclic dianhydride is selected from at least one of cyclobutanetetracarboxylic acid, cyclobutanetetracarboxylic dianhydride, cyclohexanetetracarboxylic acid, cyclohexanetetracarboxylic dianhydride, cyclopentanetetracarboxylic acid, cyclopentanetetracarboxylic dianhydride, 2,4-dimethyl-1,2,3,4-cyclobutanetetracarboxylic acid, 2,4-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, and bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride.

[0081] In some embodiments, the esterification agent is selected from at least one of 2-hydroxyethyl methacrylate, ethanol, propanol, n-butanol, hydroxypropyl methacrylate, and 2-hydroxy-1,3-propylene glycol 2-acrylate. By introducing a photosensitive group into the polyimide precursor with an esterification agent, the image forming resolution of the resin can be improved.

[0082] In some embodiments, the ratio of the molar amount of the alicyclic dianhydride to the molar amount of the esterification agent is 1: (2-2.1), specifically 1: 2, 1: 2.01, 1: 2.02, 1: 2.03, 1: 2.04, 1: 2.05, 1: 2.08 or 1: 2.1, etc., which are not limited here. Specifically, the reaction temperature of the alicyclic dianhydride and the esterification agent is room temperature, and the reaction time is 5h to 12h. The esterified solution obtained by the reaction is cooled to below 10° C. in an ice bath.

[0083] In some embodiments, the acyl chloride reagent is selected from thionyl chloride, phosphorus trichloride, phosphorus chloride, oxalyl chloride or phosgene.

[0084] In some embodiments, the ratio of the molar amount of the alicyclic dianhydride to the molar amount of the acyl chloride reagent is 1:(1-1.05), specifically 1:1, 1:1.01, 1:1.02, 1:1.03, 1:1.04 or 1:1.05, etc., and of course other values ​​within the above range may also be used. The reaction temperature of the alicyclic di-fatty acid and the acyl chloride reagent is room temperature, specifically 0°C-30°C, and a diester diacyl chloride solution is generated through sufficient reaction.

[0085] S2, adding an aromatic diamine monomer solution to the diester dichloride solution to carry out polycondensation reaction, and then performing precipitation treatment to obtain a polyamic acid ester resin.

[0086] In some embodiments, the molar ratio of the fluorine-containing aromatic diamine monomer to the fluorine-free aromatic diamine monomer is 20:80 to 60:40. Specifically, it can be 20:80, 25:75, 30:70, 35:65, 40:60, 45:55, 50:50, 55:35 or 60:40. Of course, it can also be other values ​​within the above range, which are not limited here. It should be noted that when the ratio of the two is less than 20:80, the light transmittance of the cured film is low and it is difficult to achieve high resolution. When the ratio of the two exceeds 60:40, the adhesion of the cured film to the metal will be reduced and it is easy to peel off from the metal layer.

[0087] In some embodiments, the fluorine-free aromatic diamine monomer is selected from 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 1,4-bis(4-aminophenoxy)benzene, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, 1,5-naphthalenediamine, 2,6-naphthalenediamine, bis(4-aminophenoxyphenyl)sulfone, bis(3-aminophenoxyphenyl)sulfone, bis(4-aminophenoxy)biphenyl, bis{4-(4-aminophenoxy)phenyl} At least one of ether, 4,4'-biaminobiphenyl, 2,2'-dimethyl-4,4'-biaminobiphenyl, 2,2'-diethyl-4,4'-biaminobiphenyl, 3,3'-dimethyl-4,4'-biaminobiphenyl, 3,3'-diethyl-4,4'-biaminobiphenyl, 2,2',3,3'-tetramethyl-4,4'-biaminobiphenyl, and 3,3',4,4'-tetramethyl-4,4'-biaminobiphenyl.

[0088] In some embodiments, the fluorine-containing aromatic diamine monomer is selected from at least one of 2,2'-bis(trifluoromethyl)benzidine, 2,6,2',6'-tetrakis(trifluoromethyl)benzidine, 2,2-bis[4-(3-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis(4-anilino)hexafluoropropane, 2,2-bis(3-anilino)hexafluoropropane and 2,2-bis(3-amino-4-toluoyl)hexafluoropropane.

[0089] In some embodiments, the molar weight of the alicyclic dianhydride is nA, and the molar weight of the aromatic diamine monomer is nB, 1≤nA:nB≤1.1, specifically 1:1, 1:1.01, 1:1.02, 1:1.03, 1:1.04, 1:1.05, 1:1.06, 1:1.07, 1:1.08 or 1:1.1, etc., and of course other values ​​within the above range can also be used. By controlling the molar ratio of the dianhydride monomer to the diamine monomer, the polymerization reaction is facilitated to proceed fully.

[0090] As an optional technical solution of the present application, before S2, an aromatic diamine solution is prepared, specifically comprising dissolving a preset content of aromatic diamine in an organic solvent, and stirring to form a homogeneous aromatic diamine solution.

[0091] Among them, the organic solvent is selected from at least one of N-methyl-2-pyrrolidone (abbreviated as NMP), N,N-dimethylacetamide (abbreviated as DMAc), N,N-dimethylformamide (abbreviated as DMF), dimethyl sulfoxide (abbreviated as DMSO), γ-butyrolactone (abbreviated as GBL), acetone, methyl ethyl ketone, cyclohexanone, ethyl acetate, tetrahydrofuran, dioxane, ethyl lactate, ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol and tert-butanol.

[0092] In some embodiments, the temperature of the polycondensation reaction is room temperature, specifically 0° C. to 30° C., and the duration of the polycondensation reaction is 10 h to 18 h.

[0093] In some embodiments, the precipitation step comprises:

[0094] The multi-branched polyamic acid ester resin solution after the cross-linking reaction is added into a precipitating agent for precipitation treatment, and the precipitated product is dried.

[0095] The precipitant includes at least one of water, methanol, ethanol, propanol, butanol, hexane, butyl cellosolve or toluene. Preferably, the precipitant is deionized water, methanol or ethanol, which has low toxicity and environmental pollution and is convenient for post-treatment removal.

[0096] In some embodiments, the mass ratio of the amount of the precipitant to the polyamic acid ester resin solution after the cross-linking reaction is (1-50):1; specifically, the mass ratio of the amount of the precipitant to the multi-branched polyamic acid ester resin solution after the cross-linking reaction can be 1:1, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1 or 50:1, etc., and of course, it can also be other values ​​within the above range, which is not limited here. Preferably, the mass ratio is (3-20):1.

[0097] Semiconductor packaging has strict requirements on the metal ion concentration and solid particle count of the resin material. The more times the resin solution is washed with a precipitant and the longer the soaking time, the less impurities the resin obtained. Preferably, the resin solution should be washed with a poor solvent 2 to 6 times, and each soaking time should exceed 4 hours.

[0098] In some embodiments, the drying temperature is 10°C to 150°C, specifically 10°C, 30°C, 50°C, 80°C, 100°C, 120°C or 150°C, etc., and of course other values ​​within the above range, which are not limited here. It can be understood that after the resin is washed, it should be dried in a vacuum clean oven, and controlling the drying temperature within the above range can effectively avoid resin hydrolysis and denaturation. Preferably, it is 20°C to 70°C.

[0099] <Third Aspect>

[0100] The present application provides a resin composition, which includes the resin described in the first aspect or a resin prepared by the method for preparing the resin described in the second aspect.

[0101] The polyamic acid ester in the resin composition provided in the present application can reduce the thermal expansion coefficient and stress of the resin after curing, increase the glass transition temperature and reduce the thermal expansion coefficient, and reduce the residual stress of the polyimide cured film.

[0102] In the embodiment of the present application, the resin in the resin composition can be selected according to the actual application requirements, and the resin composition may include one or more resin components or resin precursors. In some embodiments, the resin includes the resin described in the first aspect above, and may also include one or more of phenolic resin, epoxy resin, acrylic resin, benzocyclobutene resin, benzoxazole resin, and polyimide resin. In some embodiments, the resin precursor may also include one or more of phenolic resin precursor, epoxy resin precursor, acrylic resin precursor, benzocyclobutene resin precursor, benzoxazole resin precursor, and polyimide resin precursor.

[0103] In order to make the polyimide have excellent electrical properties, mechanical properties, heat resistance, moisture resistance and film retention rate, the weight average molecular weight of the resin in the resin composition can be selected from 5000 to 100000. For example, the weight average molecular weight can be 5000, 6000, 7000, 8000, 9000, 10000, 50000, 80000 or 100000, etc., which are not limited here. Preferably, the weight average molecular weight of the resin in the resin composition is 10000 to 80000; more preferably, it is 20000 to 50000.

[0104] As an optional technical solution of the present application, the resin composition further includes a photopolymerizable compound, a photopolymerization initiator, an inhibitor and an organic solvent.

[0105] In some embodiments, the photopolymerizable compound is a compound that can be cross-linked by free radicals, and the photopolymerizable compound is selected from at least one of 2-hydroxymethyl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, 2-hydroxymethyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxybutyl acrylate, glycidyl acrylate, glycidyl acrylate, glycidyl methacrylate, glycidyl methacrylate, ethylene glycol diethyl ether methacrylate, ethylene glycol diethyl ether acrylate, and polyethylene glycol methacrylate. Preferably, based on 100% by weight of the resin, the amount of the photopolymerizable compound added is 2% to 30% of the resin, and more preferably, the amount of the photopolymerizable compound added is 5% to 20% of the resin.

[0106] In some embodiments, based on the weight of the resin being 100%, the amount of the photopolymerizable compound added is 1% to 50% of the resin, specifically 1%, 5%, 10%, 15%, 19%, 23%, 25%, 30%, 35%, 40% or 50%, etc., and of course, other values ​​within the above range may also be used, which are not limited here. Preferably, the amount of the photopolymerizable compound added is 2% to 30% of the resin, and more preferably, the amount of the photopolymerizable compound added is 5% to 20% of the resin.

[0107] In some embodiments, the photopolymerization initiator is a compound that can decompose under ultraviolet light to generate free radicals. Specifically, the photopolymerization initiator is selected from benzophenone, dibenzyl ketone, 4-benzoyl-4'-methylbenzophenone, 2,2'-diethoxyacetophenone, 2-hydroxy-2-methylpropiophenone, 1-hydroxycyclohexyl phenyl ketone, thioxanthone, 2-methylthioxanthone, 2-isopropylthioxanthone, diethylthioxanthone, benzyl, benzyl dimethyl ketal, benzyl-β-methoxyethyl ketal, 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-(O-benzoyl oxime), 1-phenyl-1,2-butanedione-2-( At least one of 1-phenyl-1,2-propanedione-2-(O-methoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl)oxime, 1-phenyl-1,2-propanedione-2-(O-benzoyl)oxime, 1,3-diphenylpropanetrione-2-(O-ethoxycarbonyl)oxime, 1-phenyl-3-ethoxypropanetrione-2-(O-benzoyl)oxime, N-phenylglycine, benzoyl peroxide and α-(n-octanesulfonyloxyimino)-4-methoxybenzyl cyanide.

[0108] In some embodiments, based on the weight of the resin as 100%, the amount of the photopolymerization initiator added is 0.1% to 20% of the resin, specifically 0.1%, 0.5%, 0.8%, 1%, 2%, 5%, 10%, 12%, 13%, 15%, 18% or 20%, etc., and of course, it can also be other values ​​within the above range, which are not limited here. Preferably, the amount of the photopolymerization initiator added is 0.5% to 10% of the resin, and more preferably, the amount of the photopolymerization initiator added is 1% to 5% of the resin.

[0109] In some embodiments, the polymerization inhibitor is a compound that can quench free radicals, and the polymerization inhibitor is selected from at least one of hydroquinone, N-nitrosodiphenylamine, p-tert-butylcatechol, phenothiazine, N-phenylnaphthylamine, ethylenediaminetetraacetic acid, 1,2-cyclohexanonediaminetetraacetic acid, glycol ether diaminetetraacetic acid, 2,6-di-tert-butyl-p-cresol, 5-nitroso-8-hydroxyquinoline, 1-nitroso-2-naphthol, 2-nitroso-1-naphthol, 2-nitroso-5-(N-ethyl N-sulfopropylamino)phenol, N-nitroso-N-phenylhydroxylamine ammonium salt and N-nitroso-N(1-naphthyl)hydroxylamine ammonium salt.

[0110] In some embodiments, based on the weight of the resin as 100%, the amount of the polymerization inhibitor added is 0.01% to 10% of the resin, specifically 0.01%, 0.05%, 0.08%, 0.1%, 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8% or 10%, etc., and of course, it can also be other values ​​within the above range, which are not limited here. Preferably, the amount of the polymerization inhibitor added is 0.02% to 5% of the resin, and more preferably, the amount of the polymerization inhibitor added is 0.05% to 2% of the resin.

[0111] The resin composition provided in the present application may also contain a solvent, and the solvent includes at least one of an alcohol organic solvent, a ketone organic solvent, an ether organic solvent, an ester organic solvent, and an amide organic solvent. The present application does not specifically limit the type of solvent, as long as it can evenly dissolve the components. In order to improve the comprehensive performance of the prepared cured film, the solvent can be used alone or in combination of two or more.

[0112] In some embodiments, the solvent is selected from solvents having a boiling point of 110 to 250° C. at atmospheric pressure. Controlling the boiling point of the solvent to be above 110° C. is conducive to rapid evaporation of the solvent during coating and drying of the resin composition, thereby obtaining a uniformly coated film. The boiling point of the solvent is lower than 250° C., which is conducive to removing the residual solvent in the coating film, reducing the shrinkage of the coating film during curing, and making the cured film smoother.

[0113] In some optional embodiments, the solvent is selected from at least one of N-methyl-2-pyrrolidone (abbreviated as NMP), N,N-dimethylacetamide (abbreviated as DMAc), N,N-dimethylformamide (abbreviated as DMF), dimethyl sulfoxide (abbreviated as DMSO), γ-butyrolactone (abbreviated as GBL), acetone, methyl ethyl ketone, cyclohexanone, ethyl acetate, tetrahydrofuran, dioxane, ethyl lactate, ethylene glycol monomethyl ether, ethylene glycol dimethyl ether, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol and tert-butanol.

[0114] In some embodiments, based on 100% weight of the resin, the amount of solvent added is 100% to 1000% of the resin, preferably, the amount of solvent added is 150% to 500% of the resin, and more preferably, the amount of solvent added is 200% to 300% of the resin.

[0115] In some embodiments, the resin composition may further include an auxiliary agent, and the auxiliary agent may include a copper discoloration inhibitor, a photosensitizer, an adhesion promoter, a thermal bridging agent, and the like.

[0116] In some embodiments, based on the weight of the resin as 100%, the amount of the additive added is 0.01% to 20% of the resin, specifically 0.01%, 0.05%, 0.1%, 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5%, 8%, 10%, 12%, 15%, 18% or 20%, etc., and of course, it can also be other values ​​within the above range, which are not limited here. Preferably, the amount of the additive added is 0.05% to 15% of the resin, and more preferably, the amount of the additive added is 0.1% to 10% of the resin.

[0117] In some embodiments, based on 100% by weight of the resin, the resin composition includes 0.05% to 2% by weight of an inhibitor, 1% to 5% by weight of a photopolymerization initiator, 5% to 20% by weight of a photopolymerizable compound, and 200% to 300% by weight of a solvent.

[0118] <Fourth Aspect>

[0119] The present application provides a cured film, which is prepared from the above resin composition. An example of preparing a cured film using the resin composition is described below, but is not limited to the following method.

[0120] The resin composition solution is spin-coated on a semiconductor substrate such as a silicon substrate by spin coating, and baked at 50°C to 150°C for 2min to 10min to obtain a film with a thickness of 16μm to 20μm, and then a mask is placed on the surface, and exposed to an ultraviolet light source (I line or GHI mixed line) for 30s; cyclopentanone is used for development, and ethyl acetate is used for rinsing to obtain the corresponding patterned graphics. In a nitrogen-filled oven, the heating rate is 3°C / min, and a program heating (60°C / 1h, 80°C / 1h, 120°C / 1h, 170°C / 1h, 230°C / 1h) is used to obtain a polyimide cured film.

[0121] In order to prevent oxidative degradation of the obtained polyimide film, the imidization by heating is performed in a vacuum or inert gas.

[0122] In some embodiments, when the thickness of the cured film is 10±1 μm, the thermal expansion coefficient at 50°C to 200°C is ≤20ppm / K, and can be specifically 20ppm / K, 19.9ppm / K, 19.4ppm / K, 18.6ppm / K, 17.6ppm / K, 16.9ppm / K, 15.7ppm / K, etc., which are not limited here. The thermal expansion coefficient of the cured film prepared by the resin composition of the present application is lower than that of other cured films because the introduction of the alicyclic ring improves the heat resistance of the resin.

[0123] In some embodiments, when the thickness of the cured film is 10±1 μm, the elongation at break of the cured film is ≥50%; specifically, it can be 50%, 52%, 54%, 55%, 56%, 57%, 58%, 60%, 62%, 65% or 70%, etc., and of course, it can also be other values ​​within the above range, which is not limited here.

[0124] In some embodiments, when the thickness of the cured film is 10±1 μm, the dielectric constant at a frequency of 40 GHz is ≤2.7, and specifically can be 2.7, 2.69, 2.68, 2.67, 2.65, 2.64, 2.63, 2.62, 2.61, 2.6 or 2.59, etc., and of course can also be other values ​​within the above range, which is not limited here.

[0125] In some embodiments, when the thickness of the cured film is 10±1 μm, the transmittance at a wavelength of 450 nm in the visible light region is ≥85%, and can be specifically 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94% or 95%, etc., and of course can also be other values ​​within the above range, which is not limited here.

[0126] The present application also provides an electronic device, which includes the above-mentioned cured film.

[0127] In some embodiments, the cured film is used as a protective layer, a passivation layer, an interlayer insulating layer, a buffer layer, a planarization layer, a shielding layer or a rewiring layer in the electronic device. Specifically, it can be used in an insulating layer, a dielectric layer or a stress buffer protective layer in electronic packaging; or in the preparation of an interlayer dielectric or insulating diaphragm of a multi-layer metal wiring interconnect structure; or in the preparation of a protective layer or insulating layer of a liquid crystal display device.

[0128] The following is a further description of the embodiments of the present invention in multiple embodiments. The embodiments of the present invention are not limited to the following specific embodiments. The embodiments can be appropriately modified within the scope of the unchanged main rights.

[0129] In the following embodiments, A is as described in the subsequent embodiments, the photopolymerizable compound is tetraethylene glycol dimethacrylate, the photopolymerization initiator is 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-(O-benzoyl oxime), the inhibitor is 2,6-di-tert-butyl-p-methylphenol, the organic solvent is N,N-dimethylacetamide, and the auxiliary agent is a photosensitizer, 2,6-bis(4'-diethylaminobenzylidene)cyclohexanone. However, the present invention is not limited to protecting the above-mentioned specific compounds, and those that are easily associated in the industry are within the scope of protection of this application.

[0130] Example 1

[0131] (1) In a 1L three-necked round-bottom flask equipped with an electric stirrer, 39.22g of cyclobutanetetracarboxylic acid dianhydride (CBDA), 52.24g of 2-hydroxyethyl methacrylate (HEMA), 28.44g of pyridine and 235g of N-methylpyrrolidone (NMP) were added in sequence and stirred at room temperature for 6 to 10 hours to generate the corresponding CBDA-diacid dimethacrylate. The above esterification solution was cooled to below 10°C in an ice bath, and 43.60g of SOCl2 was slowly added dropwise. After the addition was completed for 30 minutes, the reaction was carried out at 10-20°C for 2 to 4 hours to generate the corresponding diacyl chloride dimethacrylate.

[0132] (2) In a 1L three-necked round-bottom flask equipped with an electric stirrer, 20.02g of 4,4'-diaminodiphenyl ether, 32.02g of 2,2'-bistrifluoromethyl-4,4'-diaminobiphenyl and 160g of N-methylpyrrolidone (NMP) were added in sequence and stirred to dissolve to form a homogeneous transparent mixed diamine solution; the mixed diamine solution was cooled to below 10°C using an ice bath, and the mixed diacyl chloride dimethacrylate prepared above was added dropwise to the mixed diamine solution for 1 hour; then the mixture was returned to room temperature and reacted at room temperature for 12 to 16 hours; 12ml of ethanol was added and the mixture was stirred for 1 hour; the reaction solution was slowly poured into 5L of deionized water to precipitate a solid, which was washed, filtered and vacuum dried to obtain a polyamic acid ester resin (PAE-1).

[0133] (3) In a Class 1000 clean room equipped with a yellow light, 40 g of the above-mentioned polyamic acid ester resin (PAE-1), 2.0 g of 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl)oxime, 0.8 g of 2,6-bis(4'-diethylaminobenzylidene)cyclohexanone, 0.04 g of 2,6-di-tert-butyl-p-methylphenol, and 4.0 g of tetraethylene glycol dimethacrylate were added to 80 g of N-methylpyrrolidone (NMP) in sequence, and stirred at room temperature for 3 h to form a homogeneous resin composition solution, and the resin composition solution was filtered using filter paper or a filter capsule to obtain a resin composition solution.

[0134] (4) Use a coating machine to spin-coat the above-mentioned resin composition solution on the surface of a 6-inch wafer; after baking at 110°C for 4 minutes, a coating with a thickness of 16-20 μm is obtained. Place a mask plate on the surface of the coating and expose it to a UV light source (i line or ghi mixed line) for 30 seconds; use cyclopentanone to develop, and then rinse with ethyl acetate to obtain the corresponding patterned graphics. In a nitrogen-filled oven, the heating rate is 3°C / min, and a programmed temperature is used (first keep it at 60°C for 1 hour, then heat it to 80°C for 1 hour, then heat it to 120°C for 1 hour, heat it to 170°C for 1 hour, and finally heat it to 230°C for 1 hour) to obtain a patterned polyimide cured film.

[0135] The polyimide cured film has a thickness of 10 μm, a dielectric constant of 2.6 at 40 GHz, a graphic resolution of 10 μm, a coefficient of thermal expansion (CTE) of 16.9 ppm / K, a glass transition temperature (Tg) of 240°C, an elongation at break of 55%, a transmittance of 85% at 450 nm, and excellent adhesion to Cu / Si.

[0136] Example 2

[0137] (1) In a 1L three-necked round-bottom flask equipped with an electric stirrer, 39.22g of cyclobutanetetracarboxylic acid dianhydride (CBDA), 52.24g of 2-hydroxyethyl methacrylate (HEMA), 28.44g of pyridine and 235g of N-methylpyrrolidone (NMP) were added in sequence and stirred at room temperature for 6 to 10 hours to generate the corresponding CBDA-diacid dimethacrylate. The above esterification solution was cooled to below 10°C in an ice bath, and 43.60g of SOCl2 was slowly added dropwise. After the addition was completed for 30 minutes, the reaction was carried out at 10-20°C for 2 to 4 hours to generate the corresponding diacyl chloride dimethacrylate.

[0138] (2) In a 1L three-necked round-bottom flask equipped with an electric stirrer, 19.83g of 4,4'-diaminodiphenylmethane, 33.62g of 2,2'-bis(trifluoromethyl)-4,4'-diaminophenyl ether and 160g of N-methylpyrrolidone (NMP) were added in sequence and stirred to dissolve to form a homogeneous transparent mixed diamine solution; the mixed diamine solution was cooled to below 10°C using an ice bath, and the above-mentioned diacyl chloride dimethacrylate was added dropwise to the mixed diamine solution for 1 hour; then the mixture was returned to room temperature and reacted at room temperature for 12 to 16 hours; 12ml of ethanol was added and the mixture was stirred for 1 hour; the reaction solution was slowly poured into 5L of deionized water to precipitate a solid, which was washed, filtered and vacuum dried to obtain a polyamic acid ester resin (PAE-2).

[0139] (3) In a Class 1000 clean room equipped with a yellow light, 40 g of the above-mentioned polyamic acid ester resin (PAE-2), 2.0 g of 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl)oxime, 0.8 g of 2,6-bis(4'-diethylaminobenzylidene)cyclohexanone, 0.04 g of 2,6-di-tert-butyl-p-methylphenol, and 4.0 g of tetraethylene glycol dimethacrylate were added to 80 g of NMP in sequence, and stirred at room temperature for 3 h to form a homogeneous resin composition solution, and the resin composition solution was filtered using filter paper or a filter capsule to obtain a resin composition solution.

[0140] (4) Use a coating machine to spin-coat the above-mentioned resin composition solution on the surface of a 6-inch wafer; after baking at 110°C for 4 minutes, a coating with a thickness of 16-20 μm is obtained. Place a mask plate on the surface of the coating and expose it to a UV light source (I line or GHI mixed line) for 30 seconds; use cyclopentanone to develop, and then rinse with ethyl acetate to obtain the corresponding patterned graphics. In a nitrogen-filled oven, the heating rate is 3°C / min, and a programmed temperature is used (first keep it at 60°C for 1 hour, then heat it to 80°C for 1 hour, then heat it to 120°C for 1 hour, continue to heat it to 170°C for 1 hour, and finally heat it to 230°C for 1 hour) to obtain a patterned polyimide cured film.

[0141] The polyimide cured film has a thickness of 10μm, a dielectric constant of 2.7 at 40GHz, a graphic resolution of 10μm, a coefficient of thermal expansion (CTE) of 19.4ppm / K, a glass transition temperature (Tg) of 243°C, an elongation at break of 54%, a transmittance of 85% at 450nm, and excellent adhesion to Cu / Si.

[0142] Example 3

[0143] (1) In a 1L three-necked round-bottom flask equipped with an electric stirrer, add 42.03g of cyclopentanetetracarboxylic acid dianhydride (CPDA), 52.24g of 2-hydroxyethyl methacrylate (HEMA), 28.44g of pyridine and 260g of N-methylpyrrolidone (NMP) in sequence, and stir at room temperature for 6 to 10 hours to generate the corresponding CPDA-diacid dimethacrylate. Cool the above esterification solution to below 10°C with an ice bath, slowly add 43.60g of SOCl2 dropwise, and after 30 minutes of dropwise addition, react at 10-20°C for 2 to 4 hours to generate the corresponding diacyl chloride dimethacrylate.

[0144] (2) In a 1L three-necked round-bottom flask equipped with an electric stirrer, 20.02g of 4,4'-diaminodiphenyl ether, 32.02g of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl and 160g of N-methylpyrrolidone (NMP) were added in sequence and stirred to dissolve to form a homogeneous transparent mixed diamine solution; the mixed diamine solution was cooled to below 10°C using an ice bath, and the mixed diacyl chloride dimethacrylate prepared above was added dropwise to the mixed diamine solution for 1 hour; then the mixture was returned to room temperature and reacted at room temperature for 12 to 16 hours; 12ml of ethanol was added and the mixture was stirred for 1 hour; the reaction solution was slowly poured into 5L of deionized water to precipitate a solid, which was washed, filtered and vacuum dried to obtain a polyamic acid ester resin (PAE-3).

[0145] (3) In a Class 1000 clean room equipped with a yellow light, 40 g of the above-mentioned polyamic acid ester resin (PAE-3), 2.0 g of 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl)oxime, 0.8 g of 2,6-bis(4'-diethylaminobenzylidene)cyclohexanone, 0.04 g of 2,6-di-tert-butyl-p-methylphenol, and 4.0 g of tetraethylene glycol dimethacrylate were added to 80 g of N-methylpyrrolidone (NMP) in sequence, and stirred at room temperature for 3 h to form a homogeneous resin composition solution, and the resin composition solution was filtered using filter paper or a filter capsule to obtain a resin composition solution.

[0146] (4) Use a coating machine to spin-coat the above-mentioned resin composition solution on the surface of a 6-inch wafer; after baking at 110°C for 4 minutes, a coating with a thickness of 16-20 μm is obtained. Place a mask plate on the surface of the coating and expose it to a UV light source (I line or GHI mixed line) for 30 seconds; use cyclopentanone to develop, and then rinse with ethyl acetate to obtain the corresponding patterned graphics. In a nitrogen-filled oven, the heating rate is 3°C / min, and a programmed temperature is used (first keep it at 60°C for 1 hour, then heat it to 80°C for 1 hour, then heat it to 120°C for 1 hour, continue to heat it to 170°C for 1 hour, and finally heat it to 230°C for 1 hour) to obtain a patterned polyimide cured film.

[0147] The polyimide cured film has a thickness of 10 μm, a dielectric constant of 2.6 at 40 GHz, a graphic resolution of 10 μm, a coefficient of thermal expansion (CTE) of 17.6 ppm / K, a glass transition temperature (Tg) of 238°C, an elongation at break of 56%, a transmittance of 86% at 450 nm, and excellent adhesion to Cu / Si.

[0148] Example 4

[0149] (1) In a 1L three-necked round-bottom flask equipped with an electric stirrer, add 44.82g of cyclohexanetetracarboxylic dianhydride (HPMDA), 52.24g of 2-hydroxyethyl methacrylate (HEMA), 28.44g of pyridine and 260g of N-methylpyrrolidone (NMP) in sequence, and stir at room temperature for 6 to 10 hours to generate the corresponding HPMDA-diacid dimethacrylate. Cool the above esterification solution to below 10°C with an ice bath, slowly add 43.60g of SOCl2 dropwise, and after 30 minutes of dropwise addition, react at 10-20°C for 2 to 4 hours to generate the corresponding diacyl chloride dimethacrylate.

[0150] (2) In a 1L three-necked round-bottom flask equipped with an electric stirrer, 19.83g of 4,4'-diaminodiphenylmethane, 33.62g of 2,2'-bis(trifluoromethyl)-4,4'-diaminophenyl ether and 160g of NMP were added in sequence and stirred to dissolve to form a homogeneous transparent mixed diamine solution; the mixed diamine solution was cooled to below 10°C using an ice bath, and the mixed diacyl chloride dimethacrylate prepared above was added dropwise to the mixed diamine solution for 1 hour; then the mixture was returned to room temperature and reacted at room temperature for 12 to 16 hours; 12ml of ethanol was added and the mixture was stirred for 1 hour; the reaction solution was slowly poured into 5L of deionized water to precipitate a solid, which was washed, filtered and vacuum dried to obtain a polyamic acid ester resin (PAE-4).

[0151] (3) In a Class 1000 clean room equipped with a yellow light, 40 g of the above-mentioned polyamic acid ester resin (PAE-4), 2.0 g of 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl)oxime, 0.8 g of 2,6-bis(4'-diethylaminobenzylidene)cyclohexanone, 0.04 g of 2,6-di-tert-butyl-p-methylphenol, and 4.0 g of tetraethylene glycol dimethacrylate were added to 80 g of NMP in sequence, and stirred at room temperature for 3 h to form a homogeneous resin composition solution, and the resin composition solution was filtered using filter paper or a filter capsule to obtain a resin composition solution.

[0152] (4) Use a coating machine to spin-coat the above-mentioned resin composition solution on the surface of a 6-inch wafer; after baking at 110°C for 4 minutes, a coating with a thickness of 16-20 μm is obtained. Place a mask plate on the surface of the coating and expose it to a UV light source (I line or GHI mixed line) for 30 seconds; use cyclopentanone to develop, and then rinse with ethyl acetate to obtain the corresponding patterned graphics. In a nitrogen-filled oven, the heating rate is 3°C / min, and a programmed temperature is used (first keep it at 60°C for 1 hour, then heat it to 80°C for 1 hour, then heat it to 120°C for 1 hour, continue to heat it to 170°C for 1 hour, and finally heat it to 230°C for 1 hour) to obtain a patterned polyimide cured film.

[0153] The polyimide cured film has a thickness of 10μm, a dielectric constant of 2.7 at 40GHz, a graphic resolution of 10μm, a coefficient of thermal expansion (CTE) of 19.9ppm / K, a glass transition temperature (Tg) of 240°C, an elongation at break of 58%, a transmittance of 87% at 450nm, and excellent adhesion to Cu / Si.

[0154] Example 5

[0155] (1) In a 1L three-necked round-bottom flask equipped with an electric stirrer, add 44.82g of dimethylcyclobutane tetracarboxylic anhydride (DMCBDA), 52.24g of 2-hydroxyethyl methacrylate (HEMA), 28.44g of pyridine and 260g of N-methylpyrrolidone (NMP) in sequence, and stir at room temperature for 6 to 10 hours to generate the corresponding DMCBDA-diacid dimethacrylate. Cool the above esterification solution to below 10°C with an ice bath, slowly add 43.60g of SOCl2 dropwise, and after 30 minutes of dropwise addition, react at 10-20°C for 2 to 4 hours to generate the corresponding diacyl chloride dimethacrylate.

[0156] (2) In a 1L three-necked round-bottom flask equipped with an electric stirrer, 21.23g of 4,4'-diaminobenzophenone, 33.43g of 2,2-bis(4-aminophenyl)hexafluoropropane and 160g of methylpyrrolidone (NMP) were added in sequence and stirred to dissolve to form a homogeneous transparent mixed diamine solution; the mixed diamine solution was cooled to below 10°C using an ice bath, and the mixed diacyl chloride dimethacrylate prepared above was added dropwise to the mixed diamine solution for 1 hour; then the mixture was returned to room temperature and reacted at room temperature for 12 to 16 hours; 12ml of ethanol was added and the mixture was stirred for 1 hour; the reaction solution was slowly poured into 5L of deionized water to precipitate a solid, which was washed, filtered and vacuum dried to obtain a polyamic acid ester resin (PAE-5).

[0157] (3) In a Class 1000 clean room equipped with a yellow light, 40 g of the above-mentioned polyamic acid ester resin (PAE-5), 2.0 g of 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl)oxime, 0.8 g of 2,6-bis(4'-diethylaminobenzylidene)cyclohexanone, 0.04 g of 2,6-di-tert-butyl-p-methylphenol, and 4.0 g of tetraethylene glycol dimethacrylate were added to 80 g of NMP in sequence, and stirred at room temperature for 3 h to form a homogeneous resin composition solution, and the resin composition solution was filtered using filter paper or a filter capsule to obtain a resin composition solution.

[0158] (4) Use a coating machine to spin-coat the above-mentioned resin composition solution on the surface of a 6-inch wafer; after baking at 110°C for 4 minutes, a coating with a thickness of 16-20 μm is obtained. Place a mask plate on the surface of the coating and expose it to a UV light source (I line or GHI mixed line) for 30 seconds; use cyclopentanone to develop, and then rinse with ethyl acetate to obtain the corresponding patterned graphics. In a nitrogen-filled oven, the heating rate is 3°C / min, and a programmed temperature is used (first keep it at 60°C for 1 hour, then heat it to 80°C for 1 hour, then heat it to 120°C for 1 hour, continue to heat it to 170°C for 1 hour, and finally heat it to 230°C for 1 hour) to obtain a patterned polyimide cured film.

[0159] The polyimide cured film has a thickness of 10μm, a dielectric constant of 2.7 at 40GHz, a graphic resolution of 10μm, a coefficient of thermal expansion (CTE) of 18.7ppm / K, a glass transition temperature (Tg) of 242°C, an elongation at break of 61%, a transmittance of 85% at 450nm, and excellent adhesion to Cu / Si.

[0160] Example 6

[0161] (1) In a 1L three-necked round-bottom flask equipped with an electric stirrer, 49.64g of bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride, 52.24g of 2-hydroxyethyl methacrylate (HEMA), 28.44g of pyridine and 260g of N-methylpyrrolidone (NMP) were added in sequence and stirred at room temperature for 6 to 10 hours to generate the corresponding bicyclo[2.2.2]oct-7-ene-2,3,5,6-diacid dimethacrylate. The above esterification solution was cooled to below 10°C in an ice bath, and 43.60g of SOCl2 was slowly added dropwise. After the addition was completed for 30 minutes, the reaction was carried out at 10-20°C for 2 to 4 hours to generate the corresponding diacyl chloride dimethacrylate.

[0162] (2) In a 1L three-necked round-bottom flask equipped with an electric stirrer, 20.02g of 4,4'-diaminodiphenyl ether, 32.02g of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl and 160g of NMP were added in sequence and stirred to dissolve to form a homogeneous transparent mixed diamine solution; the mixed diamine solution was cooled to below 10°C using an ice bath, and the mixed diacyl chloride dimethacrylate prepared above was added dropwise to the mixed diamine solution for 1 hour; then the mixture was returned to room temperature and reacted at room temperature for 12 to 16 hours; 12ml of ethanol was added and the mixture was stirred for 1 hour; the reaction solution was slowly poured into 5L of deionized water to precipitate a solid, which was washed, filtered and vacuum dried to obtain a polyamic acid ester resin (PAE-6).

[0163] (3) In a Class 1000 clean room equipped with a yellow light, 40 g of the above-mentioned polyamic acid ester resin (PAE-6), 2.0 g of 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl)oxime, 0.8 g of 2,6-bis(4'-diethylaminobenzylidene)cyclohexanone, 0.04 g of 2,6-di-tert-butyl-p-methylphenol, and 4.0 g of tetraethylene glycol dimethacrylate were added to 80 g of NMP in sequence, and stirred at room temperature for 3 h to form a homogeneous resin composition solution, and the resin composition solution was filtered using filter paper or a filter capsule to obtain a resin composition solution.

[0164] (4) Use a coating machine to spin-coat the above-mentioned resin composition solution on the surface of a 6-inch wafer; after baking at 110°C for 4 minutes, a coating with a thickness of 16-20 μm is obtained. Place a mask plate on the surface of the coating and expose it to a UV light source (I line or GHI mixed line) for 30 seconds; use cyclopentanone to develop, and then rinse with ethyl acetate to obtain the corresponding patterned graphics. In a nitrogen-filled oven, the heating rate is 3°C / min, and a programmed temperature is used (first keep it at 60°C for 1 hour, then heat it to 80°C for 1 hour, then heat it to 120°C for 1 hour, continue to heat it to 170°C for 1 hour, and finally heat it to 230°C for 1 hour) to obtain a patterned polyimide cured film.

[0165] The polyimide cured film has a thickness of 10μm, a dielectric constant of 2.7 at 40GHz, a graphic resolution of 10μm, a coefficient of thermal expansion (CTE) of 16.6ppm / K, a glass transition temperature (Tg) of 253°C, an elongation at break of 51%, a transmittance of 85% at 450nm, and excellent adhesion to Cu / Si.

[0166] Comparative Example 1

[0167] (1) In a 1L three-necked round-bottom flask equipped with an electric stirrer, add 62.05g of 3,3',4,4'-biphenyl ether tetracarboxylic dianhydride (ODPA), 52.24g of 2-hydroxyethyl methacrylate (HEMA), 28.44g of pyridine and 232g of N-methylpyrrolidone (NMP) in sequence, and stir at room temperature for 6 to 10 hours to generate the corresponding ODPA-diacid dimethacrylate. Cool the above esterification solution to below 10°C with an ice bath, slowly add 43.60g of SOCl2 dropwise, and after 30 minutes of dropwise addition, react at 10-20°C for 2 to 4 hours to generate the corresponding diacyl chloride dimethacrylate.

[0168] (2) In a 1L three-necked round-bottom flask equipped with an electric stirrer, 19.83g of 4,4'-diaminodiphenylmethane, 20.02g of 4,4'-diaminodiphenyl ether and 160g of N-methylpyrrolidone (NMP) were added in sequence and stirred to dissolve to form a homogeneous transparent mixed diamine solution; the mixed diamine solution was cooled to below 10°C using an ice bath, and the mixed diacyl chloride dimethacrylate prepared above was added dropwise to the mixed diamine solution for 1 hour; then the mixture was returned to room temperature and reacted at room temperature for 12 to 16 hours; 12ml of ethanol was added and the mixture was stirred for 1 hour; the reaction solution was slowly poured into 5L of deionized water to precipitate solids, which were washed, filtered and vacuum dried to obtain a polyamic acid ester resin (PAE-7).

[0169] (3) In a Class 1000 clean room equipped with a yellow light, 40 g of the above-mentioned polyamic acid ester resin (PAE-7), 2.0 g of 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl)oxime, 0.8 g of 2,6-bis(4'-diethylaminobenzylidene)cyclohexanone, 0.04 g of 2,6-di-tert-butyl-p-methylphenol, and 4.0 g of tetraethylene glycol dimethacrylate were added to 80 g of N-methylpyrrolidone (NMP) in sequence, and stirred at room temperature for 3 h to form a homogeneous resin composition solution, and the resin composition solution was filtered using filter paper or a filter capsule to obtain a resin composition solution.

[0170] (4) Use a coating machine to spin-coat the above-mentioned resin composition solution on the surface of a 6-inch wafer; after baking at 110°C for 4 minutes, a coating with a thickness of 16-20 μm is obtained. Place a mask plate on the surface of the coating and expose it to a UV light source (I line or GHI mixed line) for 30 seconds; use cyclopentanone to develop, and then rinse with ethyl acetate to obtain the corresponding patterned graphics. In a nitrogen-filled oven, the heating rate is 3°C / min, and a programmed temperature is used (first keep it at 60°C for 1 hour, then heat it to 80°C for 1 hour, then heat it to 120°C for 1 hour, continue to heat it to 170°C for 1 hour, and finally heat it to 230°C for 1 hour) to obtain a patterned polyimide cured film.

[0171] The polyimide cured film has a thickness of 10 μm, a dielectric constant of 3.5 at 40 GHz, a graphic resolution of 25 μm, a coefficient of thermal expansion (CTE) of 35.3 ppm / K, a glass transition temperature (Tg) of 218°C, an elongation at break of 45%, a transmittance of 43% at 450 nm, and general adhesion to Cu / Si.

[0172] Comparative Example 2

[0173] (1) In a 1L three-necked round-bottom flask equipped with an electric stirrer, 39.22g of cyclobutanetetracarboxylic acid dianhydride (CBDA), 52.24g of 2-hydroxyethyl methacrylate (HEMA), 28.44g of pyridine and 235g of N-methylpyrrolidone (NMP) were added in sequence and stirred at room temperature for 6 to 10 hours to generate the corresponding CBDA-diacid dimethacrylate. The above esterification solution was cooled to below 10°C in an ice bath, and 43.60g of SOCl2 was slowly added dropwise. After the addition was completed for 30 minutes, the reaction was carried out at 10-20°C for 2 to 4 hours to generate the corresponding diacyl chloride dimethacrylate.

[0174] (2) In a 1L three-necked round-bottom flask equipped with an electric stirrer, 36.06g of 4,4'-diaminodiphenyl ether (ODA), 2.16g of p-phenylenediamine and 160g of N-methylpyrrolidone (NMP) were added in sequence and stirred to dissolve to form a homogeneous transparent mixed diamine solution; the mixed diamine solution was cooled to below 10°C using an ice bath, and the mixed diacyl chloride dimethacrylate prepared in Example 1 was added dropwise to the mixed diamine solution for 1 hour; then the room temperature was restored and the mixture was reacted at room temperature for 12 to 16 hours; 12ml of ethanol was added and the mixture was stirred for 1 hour; the reaction solution was slowly poured into 5L of deionized water to precipitate a solid, which was washed, filtered and vacuum dried to obtain a polyamic acid ester resin (PAE-8).

[0175] (3) In a Class 1000 clean room equipped with a yellow light, 40 g of the above-mentioned polyamic acid ester resin (PAE-8), 2.0 g of 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl)oxime, 0.8 g of 2,6-bis(4'-diethylaminobenzylidene)cyclohexanone, 0.04 g of 2,6-di-tert-butyl-p-methylphenol, and 4.0 g of tetraethylene glycol dimethacrylate were added to 80 g of NMP in sequence, and stirred at room temperature for 3 h to form a homogeneous resin composition solution, and the resin composition solution was filtered using filter paper or a filter capsule to obtain a resin composition solution.

[0176] (4) Use a coating machine to spin-coat the above-mentioned resin composition solution on the surface of a 6-inch wafer; after baking at 110°C for 4 minutes, a coating with a thickness of 16-20 μm is obtained. Place a mask plate on the surface of the coating and expose it to a UV light source (i line or ghi mixed line) for 30 seconds; use cyclopentanone to develop, and then rinse with ethyl acetate to obtain the corresponding patterned graphics. In a nitrogen-filled oven, the heating rate is 3°C / min, and a programmed temperature is used (first keep it at 60°C for 1 hour, then heat it to 80°C for 1 hour, then heat it to 120°C for 1 hour, heat it to 170°C for 1 hour, and finally heat it to 230°C for 1 hour) to obtain a patterned polyimide cured film.

[0177] The polyimide cured film has a thickness of 10 μm, a dielectric constant of 3.2 at 40 GHz, a graphic resolution of 15 μm, a coefficient of thermal expansion (CTE) of 25.0 ppm / K, a glass transition temperature (Tg) of 250°C, an elongation at break of 41%, a transmittance of 75% at 450 nm, and excellent adhesion to Cu / Si.

[0178] Comparative Example 3

[0179] (1) In a 1L three-necked round-bottom flask equipped with an electric stirrer, add 44.82g of cyclohexanetetracarboxylic dianhydride (HPMDA), 52.24g of 2-hydroxyethyl methacrylate (HEMA), 28.44g of pyridine and 235g of N-methylpyrrolidone (NMP) in sequence, and stir at room temperature for 6 to 10 hours to generate the corresponding HPMDA-diacid dimethacrylate. Cool the above esterification solution to below 10°C with an ice bath, slowly add 43.60g of SOCl2 dropwise, and after 30 minutes of dropwise addition, react at 10-20°C for 2 to 4 hours to generate the corresponding diacyl chloride dimethacrylate.

[0180] (2) In a 1L three-necked round-bottom flask equipped with an electric stirrer, 64.04g of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl and 160g of N-methylpyrrolidone (NMP) were added in sequence and stirred to dissolve to form a homogeneous transparent mixed diamine solution; the mixed diamine solution was cooled to below 10°C using an ice bath, and the mixed diacyl chloride dimethacrylate prepared in Example 1 was added dropwise to the mixed diamine solution for 1 hour; then the mixture was restored to room temperature and reacted at room temperature for 12 to 16 hours; 12ml of ethanol was added and the mixture was stirred for 1 hour; the reaction solution was slowly poured into 5L of deionized water to precipitate solids, which were washed, filtered, and vacuum dried to obtain a polyamic acid ester resin (PAE-9).

[0181] (3) In a Class 1000 clean room equipped with a yellow light, 40 g of the above-mentioned polyamic acid ester resin (PAE-9), 2.0 g of 1-phenyl-1,2-propanedione-2-(O-ethoxycarbonyl)oxime, 0.8 g of 2,6-bis(4'-diethylaminobenzylidene)cyclohexanone, 0.04 g of 2,6-di-tert-butyl-p-methylphenol, and 4.0 g of tetraethylene glycol dimethacrylate were added to 80 g of NMP in sequence, and stirred at room temperature for 3 h to form a homogeneous resin composition solution, and the resin composition solution was filtered using filter paper or a filter capsule to obtain a resin composition solution.

[0182] (4) Use a coating machine to spin-coat the above-mentioned resin composition solution on the surface of a 6-inch wafer; after baking at 110°C for 4 minutes, a coating with a thickness of 16-20 μm is obtained. Place a mask plate on the surface of the coating and expose it to a UV light source (i line or ghi mixed line) for 30 seconds; use cyclopentanone to develop, and then rinse with ethyl acetate to obtain the corresponding patterned graphics. In a nitrogen-filled oven, the heating rate is 3°C / min, and a programmed temperature is used (first keep it at 60°C for 1 hour, then heat it to 80°C for 1 hour, then heat it to 120°C for 1 hour, heat it to 170°C for 1 hour, and finally heat it to 230°C for 1 hour) to obtain a patterned polyimide cured film.

[0183] The polyimide cured film has a thickness of 10 μm, a dielectric constant of 2.6 at 40 GHz, a graphic resolution of 8 μm, a coefficient of thermal expansion (CTE) of 32.6 ppm / K, a glass transition temperature (Tg) of 225°C, an elongation at break of 54%, a transmittance of 90% at 450 nm, and poor adhesion to Cu / Si.

[0184] Test Method

[0185] 1) Resolution and shrinkage test of cured film:

[0186] The resolution of the polyimide film after exposure and development (about 16um) is observed using an MX68R optical microscope. The smallest aperture that can be opened is the resolution; the shrinkage rate of the polyimide film is measured by comparing the film thickness after curing to the film thickness after spin coating and baking at 110°C for 4 minutes.

[0187] 2) Dielectric constant test of cured film:

[0188] The dielectric constant was tested using a vector network analyzer, with a sample size of 10cm*10cm*10um, a frequency range of 40GHz, and a test temperature of room temperature.

[0189] 3) Determination of the coefficient of thermal expansion (abbreviated as CTE) and glass transition temperature (abbreviated as Tg) of the cured film:

[0190] The thermal expansion coefficient was determined using a thermomechanical analyzer TMA, with a sample size of 16mm*4mm*10um, and the temperature was raised from room temperature to 350℃ at 3℃ / min, and the thermal expansion coefficient was measured in the range of 50℃ to 200℃;

[0191] The glass transition temperature was characterized by a dynamic thermal analyzer DMA, with a sample size of 25mm*6.5mm*10um, and the temperature was increased from room temperature to 350°C at 3°C / min. The tan delta peak temperature was taken as the glass transition temperature.

[0192] 4) Determination of elongation at break of cured film:

[0193] The elongation at break of a cured film with a thickness of 10 μm was measured using a universal material testing machine to obtain a stress-strain curve method.

[0194] 5) Determination of light transmittance of cured film:

[0195] The polyimide cured film with a thickness of 10 μm was measured using a MCPD-300 multi-channel spectrometer at a light wave of 400 nm. 6) Determination of the adhesion of the cured film:

[0196] Spin-coat the prepared photosensitive resin composition on a silicon wafer (copper sheet) to form a film, heat it on a hot plate at 110°C for 4 minutes to evaporate part of the solvent, and obtain a dried composition coating. Place the film under a mask and expose it using a contact exposure machine with a 365nm mercury lamp light source, with an exposure energy range of 300-400mJ / cm 2 . The exposed film was placed in a nitrogen-filled oven at a heating rate of 3°C / min, and a programmed temperature increase (first at 60°C for 1h, then at 80°C for 1h, then at 120°C for 1h, then at 170°C for 1h, and finally at 230°C for 1h) was used to obtain a polyimide cured film with a thickness of 10um adhered to the silicon wafer (copper wafer). The cured film was cut into 10*10 areas with a grid knife, and the wafer was treated with uhast (130°C, 85% RH, 230kPa) for 96h, and the wafer was peeled off with 3M tape. The case where there was no PI film peeling on the silicon wafer and the copper wafer was recorded as "+++", the case where the PI film peeling on the copper wafer or the silicon wafer was within 5% was recorded as "++", the case where the PI film peeling on the copper wafer or the silicon wafer was within 10% was recorded as "+", and the case where the PI film peeling on the copper wafer or the silicon wafer was more than 10% was recorded as "-".

[0197] The polyimide films prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were subjected to the above tests respectively, and the test results are shown in Table 1:

[0198] Table 1. Main properties of photosensitive polyimide film

[0199]

[0200] Table 1 shows the main performance parameters of the photosensitive polyimide films in Examples 1 to 6 and Comparative Examples 1 to 3.

[0201] It can be seen from the data in Table 1 that the thermal expansion coefficient of the cured film corresponding to Examples 1-6 is ≤20ppm / K, the elongation at break of the cured film is ≥50%, the dielectric constant of the cured film at a frequency of 40GHz is ≤2.7, and the transmittance of the cured film at a wavelength of 450nm in the visible light region is ≥85%. It can be seen that while reducing the dielectric constant of the cured film, the cured film can have excellent tensile properties (elongation at break), heat resistance (glass transition temperature), patterning performance (patterning resolution) and adhesion, thereby improving the reliability of the packaging structure or electronic device containing the cured film.

[0202] Comparative Example 1, compared with Example 1, due to the use of 3,3',4,4'-biphenyl ether tetracarboxylic dianhydride, which is an aromatic compound rather than a polyalicyclic compound, the prepared polyamic acid ester does not contain a tetravalent alicyclic organic group, and the resin has excellent heat resistance, but the thermal expansion coefficient of the cured film is greatly increased, the patterning performance and tensile performance are significantly reduced compared with Example 1, and the dielectric constant is also higher.

[0203] In Comparative Example 2, compared with Example 1, since the diamine monomer used is not a fluorine-containing aromatic diamine monomer, the prepared polyamic acid ester resin does not contain a fluorine-containing divalent aromatic organic group, the glass transition temperature of the resin increases, the rigidity of the resin is enhanced, and the flexibility decreases, resulting in a decrease in the tensile properties compared to Example 1, and the dielectric constant of the cured film is also maintained at a high level.

[0204] In Comparative Example 3, compared with Example 4, due to the use of a single fluorine-containing aromatic diamine monomer, the adhesion of the cured film to the metal is reduced, and it is easy to peel off from the metal layer. The patterning performance of the cured film is also reduced, and the heat resistance is also reduced.

Claims

1. A resin, characterized in that The resin is a compound represented by formula I; wherein R1 and R2 are each independently a hydrogen atom, a hydrocarbon group, an aryl group, an aromatic hydrocarbon group or a monovalent organic group, and R1 and R2 are not hydrogen atoms at the same time; X is selected from tetravalent alicyclic organic groups; Y1 is selected from divalent aromatic organic groups; Y2 is selected from fluorine-containing divalent aromatic organic groups; n is a natural number selected from 30 to 150, and m is a natural number selected from 30 to 150.

2. The resin according to claim 1, characterized in that The X is selected from at least one of the following structures: 。 3. The resin according to claim 1, characterized in that The Y1 is selected from the group of the structure shown in formula II; In Formula II, Z is selected from any one of -CH2-, -O-, -C=O- and -S=O-.

4. The resin according to claim 1, characterized in that The Y2 is selected from at least one of the following structures: 。 5. The resin according to claim 1, characterized in that At least one of R1 and R2 is selected from a monovalent organic group without a saturated bond.

6. A method for preparing the resin according to any one of claims 1 to 5, characterized in that: The method comprises: Under the protection of inert gas, alicyclic dianhydride is reacted with an esterification agent to generate alicyclic diester diacid, and then alicyclic diester diacid is reacted with an acyl chloride agent to generate a diester diacid chloride solution; Aromatic diamine monomer solution is added to the diester dichloride solution to carry out polycondensation reaction, followed by precipitation treatment to obtain polyamic acid ester resin, wherein the aromatic diamine monomer includes fluorine-containing aromatic diamine monomer and fluorine-free aromatic diamine monomer.

7. The preparation method according to claim 6, characterized in that: The method satisfies at least one of the following characteristics: (1) The alicyclic dianhydride is at least one selected from cyclobutanetetracarboxylic acid, cyclobutanetetracarboxylic dianhydride, cyclohexanetetracarboxylic acid, cyclohexanetetracarboxylic dianhydride, cyclopentanetetracarboxylic acid, cyclopentanetetracarboxylic dianhydride, 2,4-dimethyl-1,2,3,4-cyclobutanetetracarboxylic acid, 2,4-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, and bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride; (2) the esterification agent is selected from at least one of 2-hydroxyethyl methacrylate, ethanol, propanol, n-butanol, hydroxypropyl methacrylate, and 2-hydroxy-1,3-propylene glycol 2-acrylate; (3) the ratio of the molar amount of the alicyclic dianhydride to the molar amount of the esterification agent is 1:(2-2.1); (4) The acyl chloride reagent is selected from thionyl chloride, phosphorus trichloride, phosphorus chloride, oxalyl chloride or phosgene; (5) The ratio of the molar amount of the alicyclic dianhydride to the molar amount of the acyl chloride reagent is 1:(1-1.05); (6) The aromatic diamine monomer is selected from 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 1,4-bis(4-aminophenoxy)benzene, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, 1,5-naphthalenediamine, 2,6-naphthalenediamine, bis(4-aminophenoxyphenyl)sulfone, bis(3-aminophenoxyphenyl)sulfone, bis(4-aminophenoxy)biphenyl, bis{4-(4-aminophenoxy)phenyl}ether, 4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 2,2'-diethyl-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,3 At least one of '-diethyl-4,4'-diaminobiphenyl, 2,2',3,3'-tetramethyl-4,4'-diaminobiphenyl, 3,3',4,4'-tetramethyl-4,4'-diaminobiphenyl, 2,2'-bis(trifluoromethyl)benzidine, 2,6,2',6'-tetrakis(trifluoromethyl)benzidine, 2,2-bis[4-(3-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis(4-anilino)hexafluoropropane, 2,2-bis(3-anilino)hexafluoropropane and 2,2-bis(3-amino-4-toluoyl)hexafluoropropane; (7) The molar ratio of the fluorine-containing aromatic diamine monomer to the fluorine-free aromatic diamine monomer is 20:80 to 60:40; (8) The molar weight of the alicyclic dianhydride is nA, and the molar weight of the aromatic diamine monomer is nB, 1≤nA:nB≤1.

1.

8. The preparation method according to claim 6, characterized in that: The steps of the precipitation treatment include: The polyamic acid ester resin solution after the cross-linking reaction is added to a precipitant for precipitation treatment, and the precipitated product is dried; wherein the precipitant includes at least one of water, methanol, ethanol, propanol, butanol, hexane, butyl cellosolve or toluene.

9. The preparation method according to claim 8, characterized in that: The method satisfies at least one of the following characteristics: (1) The mass ratio of the precipitant to the polyamic acid ester resin solution after the cross-linking reaction is (1-50):1; (2) The drying temperature is 10°C to 150°C.

10. A resin composition, characterized in that The resin composition comprises the resin according to any one of claims 1 to 5.

11. The resin composition according to claim 10, characterized in that The resin composition satisfies at least one of the following characteristics: (1) The weight average molecular weight of the resin is 5000 to 100000; (2) based on the mass of the resin being 100%, the resin composition further comprises a polymerization inhibitor in an amount of 0.01% to 10% by mass; (3) Based on 100% by weight of the resin, the resin composition further comprises 100% to 1000% by weight of a solvent, wherein the solvent comprises at least one of an alcohol organic solvent, a ketone organic solvent, an ether organic solvent, an ester organic solvent and an amide organic solvent; (4) Based on 100% by weight of the resin, the resin composition comprises 0.1% to 20% by weight of a photopolymerization initiator, wherein the photopolymerization initiator is selected from at least one of benzoin and its derivatives, acetophenone derivatives, α-hydroxyketone derivatives, acylphosphorus oxides, oxime compounds, aromatic ketone compounds and metallocene compounds; (5) Based on the mass of the resin being 100%, the resin composition further comprises a photopolymerizable compound accounting for 1% to 50% by mass; (6) The resin composition further includes a photopolymerizable compound, and the photopolymerizable compound includes at least one of 2-hydroxymethyl methacrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, 2-hydroxymethyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxybutyl acrylate, glycidyl acrylate, glycidyl acrylate, glycidyl methacrylate, glycidyl methacrylate, ethylene glycol diethyl ether methacrylate, ethylene glycol diethyl ether acrylate and polyethylene glycol methacrylate.

12. The resin composition according to claim 11, characterized in that Based on 100% by weight of the resin, the resin composition includes 0.05% to 2% by weight of a polymerization inhibitor, 1% to 5% by weight of a photopolymerization initiator, 5% to 20% by weight of a photopolymerizable compound, and 200% to 300% by weight of a solvent.

13. A cured film, characterized in that: The cured film is prepared from the resin composition according to any one of claims 10 to 12.

14. The cured film according to claim 13, characterized in that It meets at least one of the following characteristics: (1) When the thickness of the cured film is 10±1 μm, the thermal expansion coefficient at 50° C. to 200° C. is ≤20 ppm / K; (2) When the thickness of the cured film is 10±1 μm, the elongation at break of the cured film is ≥50%; (3) When the thickness of the cured film is 10±1 μm, the dielectric constant at a frequency of 40 GHz is ≤2.7; (4) When the thickness of the cured film is 10±1 μm, the transmittance at a wavelength of 450 nm in the visible light region is ≥85%.

15. An electronic device, characterized in that: The electronic device comprises the cured film according to claim 13 or 14, or the electronic device comprises a cured film formed by curing the resin composition according to any one of claims 10 to 12.

16. The electronic device according to claim 15, characterized in that: The cured film is used as a protective layer, a passivation layer, an interlayer insulating layer, a buffer layer, a planarization layer, a shielding layer, or a rewiring layer in the electronic device.